1996
DOI: 10.1046/j.1365-2567.1996.457538.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in circulating and antigen‐responsive T‐cell subpopulations post‐Mycobacterium bovis infection in cattle

Abstract: SUMMARYBovine tuberculosis is a threat to animal and human health in several countries. Greater understanding of the immunology of the disease is required to develop improved tests and vaccines. This study has used a model of bovine tuberculosis, established in the natural host, to investigate the dynamic changes that occur in the circulating T-cell subpopulations after infection. When the phenotypic composition of the peripheral blood lymphocytes was determined pre-and post-experimental infection, the respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
69
1
4

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(80 citation statements)
references
References 45 publications
6
69
1
4
Order By: Relevance
“…TNF-␣ levels from bulk lymphocytes did not correlate with depletion of WC-1 ϩ ␥/␦ T cells and were largely undetectable in macrophagedepleted splenocytes. In cattle, ␥/␦ T cells have been shown to decrease initially after infection and then increase in the peripheral circulation [34]. The data presented suggest that the pivotal role in infection for this population may arise in the transition from the acute to acquired immune response, around 21 days post infection.…”
Section: Discussionmentioning
confidence: 80%
“…TNF-␣ levels from bulk lymphocytes did not correlate with depletion of WC-1 ϩ ␥/␦ T cells and were largely undetectable in macrophagedepleted splenocytes. In cattle, ␥/␦ T cells have been shown to decrease initially after infection and then increase in the peripheral circulation [34]. The data presented suggest that the pivotal role in infection for this population may arise in the transition from the acute to acquired immune response, around 21 days post infection.…”
Section: Discussionmentioning
confidence: 80%
“…Flow cytometry of the PBMCs was performed using FACScan (EPICS ELITE ESP Coulter crop, Florida, U.S.A.) as previously described [21]. The subpopulations of lymphocytes and monocytes were identified on the basis of forward and orthogonal light scatter and were gated appropriately.…”
Section: Methodsmentioning
confidence: 99%
“…DISCUSSION CD4 + T cells are important for resistance to infection with S. Typhimurium, though the antigen specificity of this T cell response is unknown [23,[25][26][27], and there has been much reported evidence showing their roles as anti-cytozoic bacteria [20-22, 25, 28, 29] by secreting INF-γ and IL-2 from helper T (Th)-1 cells in CD4 + T cells [21,23,27]. In cases of salmonellosis, it has been reported that the number of CD4 + T cells in peripheral blood increases and that the ratio of CD4 + T cells to CD8 + T cells is increased [21,25,27]. On the other hand, in experimental oral infection in mice with S. Typhimurium, it was found that the number of γδ-T cells increases in association with the immune response [11,13].…”
Section: Facs Analysis Of Pbmcsmentioning
confidence: 99%
“…Datos experimentales y clínicos indican que el IFN-γ es esencial para la defensa del huésped contra M. tuberculosis, por lo que los defectos en la producción de IFN-γ se consideran un factor de riesgo para la infección por M. tuberculosis y la progresión de la enfermedad en humanos (7) . En bovinos infectados experimentalmente con M. bovis, se observó que la principal población celular productora de IFN-γ son los linfocitos T CD4 + de memoria, aunque los linfocitos T CD8 + también han sido identificados como productores importantes de esta citocina (8) . Las citocinas proinflamatorias IL-12, IL-18, IL-23 producidas por los macrófagos inducen la activación de los linfocitos T, estimulando así la síntesis de IFN-γ, el cual a su vez activa a los macrófagos para producir TNF-α.…”
unclassified
“…La importancia de las poblaciones de macrófagos y linfocitos T en la tuberculosis bovina se ha estudiado principalmente en ganado infectado experimentalmente (8) , por lo que el objetivo de este estudio fue identificar la capacidad de los macrófagos en el control de la infección por M. bovis y la producción de IFN-γ de los linfocitos en bovinos naturalmente infectados con este patógeno.…”
unclassified